2020
DOI: 10.1088/1757-899x/872/1/012093
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of performance and emission characteristics of diesel engine with use of rape seed oil as biodiesel

Abstract: In this paper, emission and performance characteristics of diesel fuel-engine was investigated using blending of diesel with bio diesel under steady state. Rape-seed oil was used as biodiesel and blended in diesel with different proportions of 10%, 20% and 30% by volume. The engine used in experiment was single cylinder 4-stroke diesel fuel-engine having water cooling system. Result shows that BTE decreases with more addition of bio-diesel in % fraction. For 10% blend, BTE of engine is almost same compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…However, at a high engine load, fuel dispersion in the spray, the amount of fuel placed on the walls, cylinder gas pressure and temperature, and injection duration were increased, which caused increasing HC emission . Similar research was reported by Yesilyurt et al., Maroa and Inambao, and Mehta et al who found that HC emissions decreased at a low engine load and HC emissions increased when the engine load increased. In the research of Yesilyurt et al, they studied the performance and emission analysis in diesel engines using the blend of pentanol/safflower oil biodiesel/diesel fuel by varying the engine loads such as 500, 750, 1000, and 1250 engine load/W.…”
Section: Resultssupporting
confidence: 87%
“…However, at a high engine load, fuel dispersion in the spray, the amount of fuel placed on the walls, cylinder gas pressure and temperature, and injection duration were increased, which caused increasing HC emission . Similar research was reported by Yesilyurt et al., Maroa and Inambao, and Mehta et al who found that HC emissions decreased at a low engine load and HC emissions increased when the engine load increased. In the research of Yesilyurt et al, they studied the performance and emission analysis in diesel engines using the blend of pentanol/safflower oil biodiesel/diesel fuel by varying the engine loads such as 500, 750, 1000, and 1250 engine load/W.…”
Section: Resultssupporting
confidence: 87%